1974
DOI: 10.1111/j.1748-1716.1974.tb05643.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Temperature on the Force‐Velocity Relationship in Rabbit Papillary Muscle

Abstract: EDMAN, K. A. P., ALICIA MATTIAZZI and E. NILSSON. T h e influence of ternperature on the force-velocity relationship in rabbit papillary muscle. Acta physiol. scand. 1974. 90. 750-756. T h e force-velocity relationship was determined at the moment of isometric peak twitch force in rabbit papillary muscles using the damped-release technique described previously. The analysis was carried out in each muscle at two o r three temperatures within the range 22-33" C. T h e experimental data were fitted with Hill'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 17 publications
3
4
1
1
Order By: Relevance
“…If the AP is shorter, then the duration of the L-type Ca 2+ current is also shorter and less Ca 2+ is brought into the cell. A very similar temperature dependency has been reported in other species ( Edman et al, 1974 ; Mattiazzi and Nilsson, 1976 ), in which the mechanical activity and the force–velocity relationship were measured in rabbit papillary muscle. The authors conclude that the observed decrease in contractility cannot be solely related to a decrease in the duration of Ca 2+ release, but may also be related to an increase in the rate of Ca 2+ sequestration by the SR.…”
Section: Discussionsupporting
confidence: 82%
“…If the AP is shorter, then the duration of the L-type Ca 2+ current is also shorter and less Ca 2+ is brought into the cell. A very similar temperature dependency has been reported in other species ( Edman et al, 1974 ; Mattiazzi and Nilsson, 1976 ), in which the mechanical activity and the force–velocity relationship were measured in rabbit papillary muscle. The authors conclude that the observed decrease in contractility cannot be solely related to a decrease in the duration of Ca 2+ release, but may also be related to an increase in the rate of Ca 2+ sequestration by the SR.…”
Section: Discussionsupporting
confidence: 82%
“…3, A and C) . This is consistent with the increase of peak isometric force observed in intact mammalian cardiac preparations at low temperature (Kruta, 1938 ;Trautwein and Dudel, 1954;Blinks and Koch-Weser, 1963 ;Langer and Brady, 1968;Edman et al, 1974;Mattiazzi and Nilsson, 1976).' Inference of the peak myoplasmic [free Ca 21] from the amplitude of the tension transient at pH 7.25 and 12°C ( Fig.…”
Section: Effects Ofdecreasing the Temperature On The Myofilaments Andsupporting
confidence: 86%
“…Here, SL 0 = 2.1 μm is the unloaded sarcomere length. If we assume the maximal shortening velocity of the cardiac muscle 5 , where ML is the muscle length (Edman et al, 1974 ), the maximal shortening velocity of a half-sarcomere is 5 25 5 25 1 . However, the previous consideration regarding the fluctuations during the time interval Δ t = 0.25 ns gives the average magnitude of the molecular velocity to be Δ t σ/ t ≈ 0.8 nm/ ns .…”
Section: Methodsmentioning
confidence: 99%